Deregulation of miR-183 and KIAA0101 in Aggressive and Malignant Pituitary Tumors - Roche, Magali; Wierinckx, Anne; Croze, Séverine; Rey, Catherine; Legras-Lachuer, Catherine; Morel, Anne-Pierre; Fusco, Alfredo; Raverot, Gérald; Trouillas, Jacqueline; Lachuer, Joel (Frontiers in Medicine, 2015)
Changes in microRNAs (miRNAs) expression in many types of cancer suggest that they may be involved in crucial steps during tumor progression. Indeed, miRNAs deregulation has been described in pituitary tumorigenesis, but few studies have described their role in pituitary tumor progression toward aggressiveness and malignancy. To assess the role of miRNAs within the hierarchical cascade of events in prolactin (PRL) tumors during progression, we used an integrative genomic approach to associate clinical–pathological features, global miRNA expression, and transcriptomic profiles of the same human tumors. We describe the specific down-regulation of one principal miRNA, miR-183, in the 8 aggressive (A, grade 2b) compared to the 18 non-aggressive (NA, grades 1a, 2a) PRL tumors. We demonstrate that it acts as an anti-proliferative gene by directly targeting KIAA0101, which is involved in cell cycle activation and inhibition of p53–p21-mediated cell cycle arrest. Moreover, we show that miR-183 and KIAA0101 expression significantly correlate with the main markers of pituitary tumors aggressiveness, Ki-67 and p53. These results confirm the activation of proliferation in aggressive and malignant PRL tumors compared to non-aggressive ones. Importantly, these data also demonstrate the ability of such an integrative genomic strategy, applied in the same human tumors, to identify the molecular mechanisms responsible for tumoral progression even from a small cohort of patients.